Efforts to Deal with the Impact of Adolescent Pregnancy through a Holistic Approach: A Literature Review - Rahmawati, Iis; Murtaqib, Murtaqib (KHD-Production, 2024)
Teenage pregnancy, occurring at the age of 15-19 years, is a global public health problem with negative impacts for both mother and baby. The purpose of the study is to analyze the efforts that have been made in various countries in dealing with the impact of adolescent pregnancy to obtain strategies and recommendations that have the potential to create positive changes in handling the problem of adolescent pregnancy globally. This research method uses a literature review. The literature search process carried out in this literature review uses the database Scopus with a range of publication years 2019-2023. The search was conducted using several keywords